A Study on Customer Satisfaction Analysis of Online Banking System in Guwahati City - Suherman, Sumardi; Pamungkas, Ery (Journal of Global Economy, Business and Finance, 2025)
This article focuses on the customer satisfaction towards the online banking system as in today's competitive market. Customer satisfaction plays an important role in the success of any organization. Customers are the main target for any business, and their satisfaction is the key factor in evaluating the individual perception towards products and services, particularly in the context of online banking systems. The purpose of this study is to investigate the level of customer satisfaction towards online banking systems in Guwahati City, Assam India. The study collects the data from 100 customers through a survey to accurately gauge the extent of customer satisfaction. By understanding the needs and preferences of customers in relation to various banking products and services, this research aims to shed light on the factors influencing customer satisfaction in the online banking sector. The findings from this research will provide valuable insights to banking institutions and other organizations operating in the online service domain, helping them devise strategies to improve customer satisfaction levels. Ultimately, this study contributes to enhancing the overall quality of online banking services and fostering customer loyalty, which are essential for sustained success in the market.